2022
DOI: 10.3389/fpsyt.2022.651008
|View full text |Cite
|
Sign up to set email alerts
|

A dimensional approach to affective disorder: The relations between Scl-90 subdimensions and QEEG parameters

Abstract: ObjectivesQEEG reflects neuronal activity directly rather than using indirect parameters, such as blood deoxygenation and glucose utilization, as in fMRI and PET. The correlation between QEEG spectral power density and Symptom Check List-90-R may help identify biomarkers pertaining to brain function, associated with affective disorder symptoms. This study aims at determining whether there is a relation between QEEG spectral power density and Symptom Check List-90-R symptom scores in affective disorders.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, high beta activity in F7 and F8 node of the NSSI group were lower than non-NSSI group. It might be related to hyperthymic temperament, referring to the study which showed anger is related to the increased high beta activity in F7, F8 node and some nodes in the occipital region [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, high beta activity in F7 and F8 node of the NSSI group were lower than non-NSSI group. It might be related to hyperthymic temperament, referring to the study which showed anger is related to the increased high beta activity in F7, F8 node and some nodes in the occipital region [29].…”
Section: Discussionmentioning
confidence: 99%
“…Mood periods are largely seasonal. All of this group meets at least one of the metabolic syndrome criteria according to NCEP-ATP III (National Cholesterol Education Program-Adult Treatment Panel III) 13 .…”
Section: Discussionmentioning
confidence: 99%
“…There is no linear transformation from one neuron up to the global cortical scales. Anxiety accompanied by hypervigilance; this mood reactivity was linked with irritability 13 . On the other hand, delta power, found to be associated with anxiety scores, too.…”
Section: Introductionmentioning
confidence: 99%
“…In our first study, we showed that the EEG changes that occur in mania disappear in the consecutive remission period 7 . In our second study, we examined the relationships between scl subdimensions and qeeg spectral power densities 8 . Fast wave activity was occurring as a response to slow wave activity 9 .…”
Section: Dıscussıonmentioning
confidence: 99%